2017
DOI: 10.3844/ajebasp.2017.71.80
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial and Trade Openness on Financial Development in Emerging Market Economies: The Case of Turkey

Abstract: Abstract:The study aims to examine whether the intensity of financial openness, trade openness and foreign direct investment promoted financial development in Turkey for the period 1974-2014. Three financial development indicators are used constructing the data from the World Development Indicators. Autoregressive Distributed Lag Model (ARDL) and the bounds tests are employed to show the long run relationship among variables. The empirical results suggest that financial openness and foreign direct investment h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…CAPR showed a positive and significant relationship with banks' cost of financial intermediation, signifying that greater CAPR contributes to a higher cost of intermediation. These findings fully conform with previous studies (Bazih and Vanwalleghem, 2021; Cakan, 2017; Douarin and Mickiewicz, 2017; Fu et al. , 2020).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…CAPR showed a positive and significant relationship with banks' cost of financial intermediation, signifying that greater CAPR contributes to a higher cost of intermediation. These findings fully conform with previous studies (Bazih and Vanwalleghem, 2021; Cakan, 2017; Douarin and Mickiewicz, 2017; Fu et al. , 2020).…”
Section: Resultssupporting
confidence: 94%
“…CAPR showed a positive and significant relationship with banks' cost of financial intermediation, signifying that greater CAPR contributes to a higher cost of intermediation. These findings fully conform with previous studies (Bazih and Vanwalleghem, 2021;Cakan, 2017;Douarin and Mickiewicz, 2017;Fu et al, 2020). We observed that ENTRYR has a positive and Note(s): NIM is the dependent variable in all models, where its higher values represent a higher cost of financial intermediation and vice versa.…”
Section: The Determinants Of the Banks' Cost Of Financial Intermediationsupporting
confidence: 92%
See 1 more Smart Citation
“…Financial openness, along with institutional and educational variables, explains most of the variation in financial development across countries and over time. Cakan (2017) Economic growth has a significant positive impact on financial development in ASEAN. This gives the meaning that the higher the economic growth of ASEAN countries will improve the quality of financial development in ASEAN.…”
Section: Resultsmentioning
confidence: 99%